Dialectics of Religion, Culture, and Local Beliefs: The Practice of Religious Moderation in the Sabu Tribal Community of East Nusa Tenggara - Mustolehudin; Muawanah, Siti (Jurnal Dialog, 2024)
Abstract Religious moderation is a national program that has been ongoing since Lukman Hakim Syaifudin initiated it. This program is being carried out throughout Indonesia, including on Sabu Island. This island is the outermost island located in East Nusa Tenggara. This study aims to explore the practice of religious moderation among the Sabu tribe. The data for this study was collected through interviews, observations, and a literature review. Research results show that religious moderation among the Sabu tribe has been practised for a very long time. The Sabu community previously mainly consisted of followers of ancestral religions. Then, after the arrival of the Dutch colonisers, there was a conversion of religion. They converted to Christianity, Catholicism, Islam, and Hindu-Buddhism. Although they have changed their religion, their religious rituals are still deeply intertwined with local spirituality (Jingitiu). Similarly, although the followers of Islam are a minority on Sabu Island, practices of harmonious living are evident in daily life. For example, the construction of the An-Nur mosque, the only place of worship for Muslims on the island, received significant support from the Sabu ethnic community during its early development. Similarly, during the Eid al-Adha celebration, the slaughtering of sacrificial animals and the distribution of the meat were also assisted by the non-Muslim community.